Evolution of the ventral midline in insect embryos. - Zinzen, R.P.; Cande, J.; Ronshaugen, M.; Papatsenko, D.; Levine, M. (Developmental Cell, 2006)
The ventral midline is a source of signals that pattern the nerve cord of insect embryos. In dipterans such as the fruitfly Drosophila melanogaster (D. mel.) and the mosquito Anopheles gambiae (A. gam.), the midline is narrow and spans just 1-2 cells. However, in the honeybee, Apis mellifera (A. mel.), the ventral midline is broad and encompasses 5-6 cells. slit and other midline-patterning genes display a corresponding expansion in expression. Evidence is presented that this difference is due to divergent cis regulation of the single-minded (sim) gene, which encodes a bHLH-PAS transcription factor essential for midline differentiation. sim is regulated by a combination of Notch signaling and a Twist (Twi) activator gradient in D. mel., but it is activated solely by Twi in A. mel. We suggest that the Twi-only mode of regulation--and the broad ventral midline--represents the ancestral form of CNS patterning in Holometabolous insects.